Impact of the timing of first appropriate shock on outcomes in patients with an implantable cardioverter‐defibrillator: Early versus late. Issue 1 (1st December 2022) - Kishihara, Makoto; Hattori, Hidetoshi; Suzuki, Atsushi; Kanai, Miwa; Kataoka, Shohei; Yazaki, Kyoichiro; Kikuchi, Noriko; Yagishita, Daigo; Minami, Yuichiro; Yamaguchi, Junichi; Shoda, Morio; Hagiwara, Nobuhisa
Abstract: Background: Appropriate implantable cardioverter‐defibrillator (ICD) shocks are associated with an increased risk of mortality and heart failure (HF) events. The first appropriate shock may occur late after implantation. However, whether the timing of the first appropriate shock influences prognosis is unknown. This study aimed to evaluate the clinical significance of the timing of the first appropriate shock in patients with ICD. Methods: This retrospective and observational study enrolled 565 consecutive ICD patients. Patients who received an appropriate shock were divided into the early group (first appropriate shock <1 year after ICD implantation) and late group (first appropriate shock ≥1 year after ICD implantation). All‐cause mortality was compared between the two groups. Results: Over a median follow‐up of 5.6 years, 112 (19.8%) patients received an appropriate shock, including 32 patients (28.6%) in the early group and 80 patients (71.4%) in the late group. Comparisons of baseline characteristics at ICD implantation revealed that the late group was more likely to receive cardiac resynchronization therapy (66.3% vs. 31.3%, p  < 0.001), ICD for primary prevention (60.0% vs. 31.3%, p  = 0.001), and angiotensin‐converting enzyme inhibitor or angiotensin‐receptor blocker treatment (88.8% vs. 71.9%, p  = 0.028). Survival after shock was significantly worse in the late group than in the early group ( p  = 0.027). In multivariable Cox proportional hazards analysis, the late group had an increased risk of all‐cause mortality compared with the early group (HR: 2.22; 95% CI 1.01–4.53 ; p  = 0.029). In both groups, the most common cause of death was HF. Conclusions: Late occurrence of the first appropriate ICD shock was associated with a worse prognosis compared with early occurrence of the first appropriate shock. Cardiac death was the most common cause of death in patients who experienced late occurrence of the first appropriate ICD shock, resulting from HF in most cases.